Investment and Growth Dynamics : An Empirical Assessment Applied to Benin - Samake, Issouf (IMF Working Papers; Working Paper, 2008)
We investigate the nexus of public and private investment and assess the impact of both types of investment on growth. Using annual data for 1965-2005, we employ a coherent set of structural VAR outputs to model investment and growth in Benin. We find that in addition to institutional and regulatory developments, public investment and private capital formation facilitated by access to financial services have a significant impact on growth. The analysis supports the crowding-in effect of public investment. It also confirms that the slow pace of improvement in Benin's economic freedom index, which reflects its relatively weak institutions and slow pace of reform, deters private investment. From the cointegration regressions, the speed-of-adjustment analysis suggests that 27 percent of the deviation of GDP from its long-run equilibrium is corrected every year, which implies that it takes two to three years to cut the gap in half.